Diseño de una granja agroecológica demostrativa en la microcuenca El Limón de la ciudad de Zamora, con fines de conservación y desarrollo - Morocho Benítez, Dalton Danilo (2015)
The current environmental problems and improper use of renewable natural resources are partly due to the way of occupying space and its misuse. The conservation of watersheds is highly complex due to the diversity of factors to consider in identifying the problems and consequences and design solutions, including social actors, with their varied interests. The micro basin "Lemon" is located in the northeastern part of the city of Zamora in the urban parish Lemon thereof which is surrounded by a varied vegetation and gives water to a lot of living things, is why important is proper management and conservation of this area in recent years has been neglected part of the population of the area of direct influence. Thus the objective that guided the development of the work was to have a demonstrative agro-ecological farm in micro watershed El Limón, which will constitute a baseline for the implementation of the ordinance for the protection of water resources in the city of Zamora. Aware of environmental problems such as hauling and sediment transport that occurs in the micro watershed "Lemon", the need for research on how to conserve soil and improve current management given by the will planted farmers in the micro basin "Lemon" The watershed "Lemon" is of importance for being the provisory of water to the city of Zamora and space for agriculture and livestock. For this reason, titling project, aims to design a Agroecológica Demonstration Farm, which serves as a model for family living micro watersheds of the canton, or others interested in the sustainable management of natural resources, respecting the environment and developing agricultural activities that allow them to produce healthy and diversified food, contributing to food sovereignty of families, considered one of the fundamental human rights for Good Living